P102 The utility of radioisotope bone scans in the liver transplant assessment for hepatocellular carcinoma. (16th November 2010) - Sheikh, K; Warbey, V; O'Beirne, J; Burroughs, A; Patch, D; Thorburn, D
Abstract : Introduction: The incidence of skeletal metastases from hepatocellular carcinoma (HCC) is estimated to be 2–16%. It is well established that radioisotope bone scans can detect cancer earlier than cross sectional imaging. The role of bone scans in pre-transplant assessment has been discussed in the literature but its place in the assessment algorithm is not clearly established. Aim: The aim of this study is to determine the utility of radioisotope bone scans in patients with a diagnosis of HCC undergoing transplant pre-assessment. Method: Radioisotope bone scan results were reviewed for all patients undergoing liver transplant assessment for HCC at our unit from 1989 to 2009. Patients were initially selected for transplant assessment based on favourable HCC staging on cross sectional imaging. Patients undergoing bone scan had the result reviewed retrospectively as normal or abnormal. All abnormal scans we then reassessed against all available imaging and classified as showing benign or malignant changes. Patient outcomes were considered in relation to bone scan results. Results: During this period 216 patients with a primary or secondary diagnosis of HCC were assessed for liver transplantation. Two hundred and three patients were listed for transplant and 148 were eventually transplanted. The results of their bone scans are as below (Abstract P102 Table 1 ). Amongst patients listed for transplant, 22 (11%) cases had abnormal bone scans with 12 cases in transplanted group showing false positive results for reasons including degenerative changes, healing traumatic fractures and tracer uptake in gynaecomastia. One patient had a scan with high suspicion for bony secondaries. This patient initially listed for transplant was removed from the list due to active substance misuse, and subsequently became too ill before bony abnormalities could be confirmed. The recurrence rates of HCC were 12.5 % in transplanted patients who underwent bone scans and 9% in those transplanted without a bone scan. Conclusion: Bone scans were not performed as rigorously as expected with 40% of listed patients with no prior radioisotope imaging. However there were no significant differences in recurrence rates in those that did and did not have bones scans. In a population of patients assessed for liver transplant with cross sectional imaging indicating HCC to be within transplant criteria bone scans had a false positive rate of 18% (24/131). The result of bone scanning did not influence the decision to list with only 1 patient exhibiting feature of bony metastases. This patient was subsequently removed from the list for other reasons.